2012
DOI: 10.1007/s11676-012-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen retranslocation, allocation, and utilization in bare root Larix olgensis seedlings

Abstract: We quantified biomass accumulation and nitrogen (N) retranslocation, allocation, and utilization of Changbai larch (Larix olgensis) seedlings subjected to four fertilization treatments (24, 59, 81, 117 kg⋅ha -1 N) with an unfertilized control during summer and autumn 2009. Ammonium phosphate (18-46-0) was the fertilizer used in all treatments.On both sampling dates, the needles had greater biomass and N content than new (2009) stems and old (2008) stems, and coarse, medium and fine roots (diameters of >5, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…On average, 79%, 50%, and 6% of stored nitrogen was retranslocated to new organs at 30, 60, and 180 days after transplanting, respectively, indicating that nitrogen retranslocation declined with time as the root system expanded, improving nitrogen uptake and reducing the reliance on nitrogen redistribution [9,27]. We found that the new growth of B. alnoides plants was dependent on internal nitrogen cycling (50-79%) in the first two months after transplanting.…”
Section: Nutrient Loadingmentioning
confidence: 77%
See 4 more Smart Citations
“…On average, 79%, 50%, and 6% of stored nitrogen was retranslocated to new organs at 30, 60, and 180 days after transplanting, respectively, indicating that nitrogen retranslocation declined with time as the root system expanded, improving nitrogen uptake and reducing the reliance on nitrogen redistribution [9,27]. We found that the new growth of B. alnoides plants was dependent on internal nitrogen cycling (50-79%) in the first two months after transplanting.…”
Section: Nutrient Loadingmentioning
confidence: 77%
“…High rates of nitrogen retranslocation were also reported in black walnut (Juglans nigra L.) (68-83%) in sand culture for 90 days [10] and P. tremuloides (73-80%) on two reconstructed soils during the first growing season [20]. However, only 32% of nitrogen was remobilized to new growth sinks in Q. rubra [28] over 90 days in a greenhouse, indicating tree species vary widely in terms of the contribution of nitrogen retranslocation required to meet the total sink demand [8,9,26]. As the nitrogen retranslocation capacity might be species dependent and change over time [10,13] (we only explored one B. alnoides clone for six months after transplanting), long-term field experiments on tree species should be conducted to further test the utility of nursery nutrient loading.…”
Section: Nutrient Loadingmentioning
confidence: 85%
See 3 more Smart Citations